2010
DOI: 10.1038/emboj.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative activation loop among SWI/SNF, γ-H2AX and H3 acetylation for DNA double-strand break repair

Abstract: Although recent studies highlight the importance of histone modifications and ATP-dependent chromatin remodelling in DNA double-strand break (DSB) repair, how these mechanisms cooperate has remained largely unexplored. Here, we show that the SWI/SNF chromatin remodelling complex, earlier known to facilitate the phosphorylation of histone H2AX at Ser-139 (S139ph) after DNA damage, binds to c-H2AX (the phosphorylated form of H2AX)-containing nucleosomes in S139ph-dependent manner. Unexpectedly, BRG1, the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
255
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(268 citation statements)
references
References 51 publications
11
255
2
Order By: Relevance
“…This indicated that histone acetylation by CBP or p300 at DSB sites facilitates the recruitment of the SWI/SNF complex. This result is consistent with a report that nucleosomes containing gH2AX, and histone H3 with mutations in the acetylation sites, lack the ability to interact with the SWI/SNF complex (Lee et al, 2010). In summary, the present results strongly indicate that the CBP and p300 proteins function as HATs for histone H3 and H4 at DSB sites and facilitate the recruitment of the SWI/SNF chromatin remodeling complex.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This indicated that histone acetylation by CBP or p300 at DSB sites facilitates the recruitment of the SWI/SNF complex. This result is consistent with a report that nucleosomes containing gH2AX, and histone H3 with mutations in the acetylation sites, lack the ability to interact with the SWI/SNF complex (Lee et al, 2010). In summary, the present results strongly indicate that the CBP and p300 proteins function as HATs for histone H3 and H4 at DSB sites and facilitate the recruitment of the SWI/SNF chromatin remodeling complex.…”
Section: Discussionsupporting
confidence: 93%
“…This was confirmed by our system. DNA damage-induced acetylation of N-terminal lysines 9, 14, 18, 23 and 56 within histone H3 in mammalian cells was observed by immunoblot analysis (Das et al, 2009;Tjeertes et al, 2009;Yuan et al, 2009;Lee et al, 2010;Miller et al, 2010). However, the results were controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruitment of ATP-dependent chromatin remodeling complexes to DSBs (Ray et al 2009;Lee et al 2010;Qi et al 2015) and the remodeling of the surrounding chromatin occur on a timescale similar to that of H2A phosphorylation. Moreover, it has been shown that the phosphorylation of Ies4 (a subunit of the INO80 chromatin remodeling complex) by Mec1/ Tel1 in response to DNA damage directs INO80 function toward checkpoint regulation (Morrison et al 2007).…”
mentioning
confidence: 99%